2018
DOI: 10.1186/s13046-018-0965-2
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatocellular carcinoma-derived exosomal miRNA-21 contributes to tumor progression by converting hepatocyte stellate cells to cancer-associated fibroblasts

Abstract: BackgroundHepatocellular carcinoma (HCC) remains a global challenge due to its high morbidity and mortality rates as well as poor response to treatment. The communication between tumor-derived elements and stroma plays a critical role in facilitating cancer progression of HCC. Exosomes are small extracellular vesicles (EVs) that are released from the cells upon fusion of multivesicular bodies with the plasma membrane. There is emerging evidence indicating that exosomes play a central role in cell-to-cell commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
267
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(271 citation statements)
references
References 50 publications
(47 reference statements)
2
267
2
Order By: Relevance
“…Immunosuppressive [125] miR-24-3p NPC Immunosuppressive [126] miR-891a NPC Immunosuppressive [126] miR-106a-5p NPC Immunosuppressive [126] miR-20a-5p NPC Immunosuppressive [126] miR-1908 NPC Immunosuppressive [126] TAMs miR-222-3p EOC Immunosuppressive [127] miR-940 EOC Immunosuppressive [128] miR-21-3p EOC Immunosuppressive [129] miR-125b-5p EOC Immunosuppressive [129] miR-181d-5p EOC Immunosuppressive [129] miR-21 Head and neck cancer Immunosuppressive [130] miR-1246 Colon cancer Immunosuppressive [131] miR-16 Breast cancer Immunostimulatory [132] MDSCs miR-107 Gastric cancer Immunosuppressive [133] miR-21 OSCC Immunosuppressive [134] miR-21 Glioma Immunosuppressive [135] miR-10a Glioma Immunosuppressive [135] miR-29a Glioma Immunosuppressive [136] miR-92a Glioma Immunosuppressive [136] miR-155 CLL Immunosuppressive [137] CAFs miR-27a Gastric cancer Immunosuppressive [138] miR-1247-3p HCC Immunosuppressive [139] miR-21 HCC Immunosuppressive [140] NPC nasopharyngeal carcinoma, TAM tumor-associated macrophage, EOC epithelial ovarian cancer, MDSC myeloid-derived suppressor cell, OSCC oral squamous cell carcinoma, CLL chronic lymphocytic leukemia, CAF cancer-associated fibroblast, HCC hepatocellular carcinoma M2-like phenotype and suppressing the expression of M1 phenotype-associated markers [130]. Similarly, Cooks et al observed that cancer cells harboring TP53 mutation could reprogram neighboring TAMs into pro-tumor state via secreting miR-1246-enriched exosomes [131].…”
Section: Effector T Cells Mir-690 Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive [125] miR-24-3p NPC Immunosuppressive [126] miR-891a NPC Immunosuppressive [126] miR-106a-5p NPC Immunosuppressive [126] miR-20a-5p NPC Immunosuppressive [126] miR-1908 NPC Immunosuppressive [126] TAMs miR-222-3p EOC Immunosuppressive [127] miR-940 EOC Immunosuppressive [128] miR-21-3p EOC Immunosuppressive [129] miR-125b-5p EOC Immunosuppressive [129] miR-181d-5p EOC Immunosuppressive [129] miR-21 Head and neck cancer Immunosuppressive [130] miR-1246 Colon cancer Immunosuppressive [131] miR-16 Breast cancer Immunostimulatory [132] MDSCs miR-107 Gastric cancer Immunosuppressive [133] miR-21 OSCC Immunosuppressive [134] miR-21 Glioma Immunosuppressive [135] miR-10a Glioma Immunosuppressive [135] miR-29a Glioma Immunosuppressive [136] miR-92a Glioma Immunosuppressive [136] miR-155 CLL Immunosuppressive [137] CAFs miR-27a Gastric cancer Immunosuppressive [138] miR-1247-3p HCC Immunosuppressive [139] miR-21 HCC Immunosuppressive [140] NPC nasopharyngeal carcinoma, TAM tumor-associated macrophage, EOC epithelial ovarian cancer, MDSC myeloid-derived suppressor cell, OSCC oral squamous cell carcinoma, CLL chronic lymphocytic leukemia, CAF cancer-associated fibroblast, HCC hepatocellular carcinoma M2-like phenotype and suppressing the expression of M1 phenotype-associated markers [130]. Similarly, Cooks et al observed that cancer cells harboring TP53 mutation could reprogram neighboring TAMs into pro-tumor state via secreting miR-1246-enriched exosomes [131].…”
Section: Effector T Cells Mir-690 Melanomamentioning
confidence: 99%
“…In addition, Fang et al found that metastatic hepatocellular carcinoma cells produced exosomal miR-1247-3p which could target B4GALT3 and activate β1-integrin-NF-κB signaling pathway in CAFs [139]. Besides, Zhou et al observed that hepatocellular carcinoma enhanced the activity of CAFs by exosomal miRNA-21-PTEN-PDK1/AKT pathway [140].…”
Section: Cancer Cells-derived Exosomal Mirnas and Cancerassociated Fimentioning
confidence: 99%
“…For example, DCs loaded with exosomes and alphagalactosylceramide can significantly improve the tumor microenvironment of rats bearing gliomas and increase the median survival of rats [73]. In contrast, hepatocellular carcinoma-derived exosomes miR-21 are thought to convert normal hepatic stellate cells to cancer-associated fibroblasts, thereby promoting tumor progression, which may provide new targets for the prevention and treatment of liver cancer [74]. The latest evidence suggests that the ability of EVs to tissue regeneration is equally astonishing.…”
Section: Evs As Therapymentioning
confidence: 99%
“…sequenced and quantitated PCR and found that HCC cell‐derived exosomes transmitted miR‐103 into endothelial cells attenuated the endothelial junction integrity by downregulating VE‐Cadherin (VE‐Cad), p120‐catenin (p120) and zonula occludens 1 (Table ). Also, there is emerging evidence indicating that HCC‐derived exosomal miR‐21 targeting PTEN led to the activation of PDK1/AKT signaling in HSCs, which educated CAFs released angiogenic cytokines, including VEGF, MMP2, MMP9, bFGF and TGF‐beta (Table ) . To abate angiogenesis remains a severe challenge for tumor treatment.…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Also, there is emerging evidence indicating that HCC-derived exosomal miR-21 targeting PTEN led to the activation of PDK1/AKT signaling in HSCs, which educated CAFs released angiogenic cytokines, including VEGF, MMP2, MMP9, bFGF and TGF-beta (Table 1). 54 To abate angiogenesis remains a severe challenge for tumor treatment. Wang et al 55 examined the expression of lncRNA-APC1 and unveiled that lncRNA-APC1 activated by APC suppressed CRC angiogenesis via targeting Rab5b mRNA, which could inhibit tumor angiogenesis in CRC (Table 1).…”
Section: Cancer Metastasismentioning
confidence: 99%